Adverse Psychiatric Effects Associated with Herbal Weight-Loss Products. (17th September 2015) - Bersani, F. Saverio; Coviello, Marialuce; Imperatori, Claudio; Francesconi, Marta; Hough, Christina M.; Valeriani, Giuseppe; De Stefano, Gianfranco; Bolzan Mariotti Posocco, Flaminia; Santacroce, Rita; Minichino, Amedeo; Corazza, Ornella
Abstract : Obesity and overeating are among the most prevalent health concerns worldwide and individuals are increasingly using performance and image-enhancing drugs (PIEDs) as an easy and fast way to control their weight. Among these, herbal weight-loss products (HWLPs) often attract users due to their health claims, assumed safety, easy availability, affordable price, extensive marketing, and the perceived lack of need for professional oversight. Reports suggest that certain HWLPs may lead to onset or exacerbation of psychiatric disturbances. Here we review the available evidence on psychiatric adverse effects of HWLPs due to their intrinsic toxicity and potential for interaction with psychiatric medications.